Pewarisan Tari Puspanjali Sebagai Tari Balih-balihan yang Monumental untuk Penguatan Tradisi, Budaya, dan Agama - I Wayan Sutirtha; Hendra Santosa (Jayapangus Press, 2026)
The Puspanjali dance was created by N. L. N. Swasti Wijaya Bandem in 1989 as a welcoming dance that later developed widely within various social and cultural activities of the Balinese community. Over time, this dance has been widely learned by children through dance studios (sanggar tari), thereby playing an important role in the intergenerational transmission of Balinese dance traditions. This study aims to analyze the process of transmitting the Puspanjali dance and to explain its position as one of the monumental balih-balihan dances in Bali. The research employed a qualitative descriptive method through observations conducted in several dance studios in Bali, interviews with choreographers, composers, studio instructors, and students who study the Puspanjali dance, and was supported by a literature review on systems of traditional art transmission. The results show that the transmission process of the Puspanjali dance primarily occurs through non-formal education in dance studios and is further supported by various performance activities and dance competitions. The relatively simple movement characteristics, the repetition of movement patterns, and the relatively short performance duration make this dance easy to learn for children and beginner dancers. These conditions strengthen the regeneration of dancers while also expanding the dissemination of the Puspanjali dance across various regions of Bali. With its sustainable transmission system and its relevance to the social and cultural life of the community, the Puspanjali dance not only functions as a welcoming dance but has also developed into one of the monumental balih-balihan dance works that contributes to strengthening the continuity of tradition, culture, and the religious life of the Balinese people.